Copyright courses in universities and art schools in Latin America - Charria-García, Fernando (REVISTA ELECTRONICA IBEROAMERICANA, 2022)
This document is the result of applied research on Copyright Culture, in its first documentary phase, investigated a part of the cognitive aspect of such conceptual tool in the art universities and university faculties in Latin America showing evidence of the small access that the students have about their rights as creators of works. The research was conducted in 285 universities that offer 612 programs in the arts in Latin America, finding that only 62 of them offer students courses related to copyright, although courses in human rights were accepted, understanding that copyright is part of them. It is understandable that what relates to copyright, it is directly related to the fact that it teaches students in a subject, as it is a way of knowing its content, however it is possible to think that knowledge can be acquired by other means although ideally it should be done directly by educational institutions.